The Use of Non-Prescribed Prescription Drugs and Substance Use Among College Students: A 9-Year Follow-Up Cohort Study - Busto Miramontes, Alicia; Moure-Rodriguez, Lucía; Diaz-Geada, Ainara; Carbia, Carina; Cadaveira, Fernando; Caamaño-Isorna, Francisco (Frontiers in Psychiatry, 2020)
The use of non-prescribed prescription drugs (NPPD) is common in post-modern societies and a significant proportion of youth consume NPPD concomitantly to other drugs. We studied the prevalence of this consumption among university students in Spain, and its relationship to different alcohol patterns, tobacco, and cannabis use. A cohort study among university students (n=1,380) (2005-2015) was carried out. Students completed self-administered questionnaires at initial (n=1,363,98.7%), 2 years (n=875,75%) and 9-years of follow-up (n=415,30.5%). Consumption of medicines (last 15 days), risky alcohol consumption (RC), heavy episodic drinking (HED), tobacco and cannabis use were measured. Multilevel logistic regressions for repeated measures were generated using consumption of medicines with or without medical prescription as dependent variables. Prevalence of RC, HED, tobacco and cannabis had significant reductions during the follow-up. The use of NPPD increased over time, from 35.5% and 33.3% at 18 and 22 years old, to 49.6% at 27. The highest rates were found among cannabis, tobacco, RC and HED users. For females, cannabis and RC constitute signitifant risk factors for use of NPPD. Conversely, for males, tobacco and cannabis were risk factors for such use of medicines. Later onset of alcohol consumption constitutes a protective factor for females. Our results reveal high prevalence of NPDD among university students. Those who consume NPPD are -at the same time- more likely to be alcohol, tobacco, and cannabis users than those who take medication under prescription. Preventive strategies should be reinforced and focused on this target population to decrease these high levels of poly-consumption.